Influence of reliability dimension on service quality performance in Northern Region Malaysian university academic library. - Ismail, Junaida; Ladisma @ Awis, Mahadir; Mohd Amin, Siti Hajjar; Shari, Sharunizam; Jusoff, Kamaruzaman (Canadian Academy of Oriental and Occidental Culture, 2009)
This study in particular scrutinizes the quality services in academic library.The reason for choosing academic library at Northern Region Malaysia (UiTM Kedah,UiTM Perlis, UiTM Penang, University Utara Malaysia, and UniMAP) is because these universities by virtue provide service par excellence. Thus, their implementation of quality service could be a guideline or standards to other university. One of the objectives of this study is to measure the quality service performance in academic libraries using reliability dimension. The fulfillment of quality service performance is the key to the success of every academic library. A high quality score for academic library depends on the several dimensions. The results of correlation showed that there is a significant relationship between all independent variable. Finally, this study found that reliability dimension walk out on to the high quality score given by the user from visit to visit library.